2010
DOI: 10.1128/aac.01527-09
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Activities of Three Triazoles with Caspofungin against Candida glabrata Isolates Determined by Time-Kill, Etest, and Disk Diffusion Methods

Abstract: Combinations of voriconazole, fluconazole, and itraconazole with caspofungin were evaluated against 50 Candida glabrata isolates by the time-kill, disk diffusion, and Etest methods. The majority of antifungal combinations were indifferent. By the time-kill method, synergistic activity was detected with eight (16%) of the caspofungin-voriconazole and seven (14%) of the caspofungin-fluconazole combinations, but synergy was not seen with the caspofungin-itraconazole combination. Further comparisons of the Etest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 21 publications
4
34
0
Order By: Relevance
“…The disk diffusion test was previously shown to be a valid method by which to detect synergy for combinations of vancomycin and ␤-lactam antibiotics against staphylococci with reduced susceptibility to vancomycin (8) and to detect synergistic activities of triazoles with caspofungin against Candida glabrata (12). It is more rapid, less expensive, and less labor intensive than the more commonly used time-kill or checkerboard method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disk diffusion test was previously shown to be a valid method by which to detect synergy for combinations of vancomycin and ␤-lactam antibiotics against staphylococci with reduced susceptibility to vancomycin (8) and to detect synergistic activities of triazoles with caspofungin against Candida glabrata (12). It is more rapid, less expensive, and less labor intensive than the more commonly used time-kill or checkerboard method.…”
Section: Discussionmentioning
confidence: 99%
“…The current study was designed to determine the utility of a modified disk diffusion (MDD) test to assess synergy and antagonism for combinations of vancomycin and ␤-lactam antibiotics among clinical isolates of MRSA (8,12). The CLSI checkerboard method was used as the reference for the determination of synergy.…”
mentioning
confidence: 99%
“…The combinations of antimicrobial agents against drug-resistant Candida have been studied (12)(13)(14)(15). Members of our group have shown that concomitant use of berberine (BBR; an alkaloid with a long history of medicinal use in traditional Chinese medicine [16]) and FLC is highly efficacious in killing FLC-resistant C. albicans in vitro, and the fractional inhibitory concentration (FIC) index ranges from 0.017 to 0.127 (17,18).…”
mentioning
confidence: 99%
“…There are no studies evaluating MTS performance for in vitro combination testing of Candida spp., whereas few studies used Etest method. [11][12][13][14] None of these studies present a quantitative correlation between the gradient concentration strip and microdilution method. When C. glabrata isolates were tested against amphotericin B+caspofungin combination with Etest strips placed simultaneously at 90°a ngle, the diffusion of the drugs through the agar was different resulting in dissimilar ellipse patterns and the agreement with the time-kill method was only 52%.…”
Section: Discussionmentioning
confidence: 94%
“…By contrast, other already introduced to the market products are made of plastic (non-porous), impregnated with a predefined concentration gradient of antifungal drug across 15 twofold dilutions of a conventional dilution method. Although gradient concentration strip diffusion assays have been used for in vitro antifungal combination testing against Candida spp., [11][12][13][14] a head-to-head comparison with chequerboard method exploring their reproducibility and agreement using different in vitro parameters is lacking. Furthermore, there are no studies evaluating the performance of the new paper strips for in vitro combination testing of Candida spp.…”
Section: Introductionmentioning
confidence: 99%